The Effects of Cutting Parameters on the Characteristics of Chip and Cutting Force in High-Speed Milling of A6061 Aluminum Alloy - Pham, Thi Hoa; Nguyen, Duc Toan (Old Journal, 2018)
This paper studied the formulation of chip in high-speed milling of A6061 aluminum alloy. To verify the chip formation and microstructure, experimental results of the chip morphology were derived. The capture by SEM of experimental results showed that high-speed milling produced serrated chip. From the deformation of various zone of chip surface, we can conclude that the chip deformation directly effect on the friction at tool and chip contact during in high-speed milling for A6061 aluminum alloy. In this study, the effects of cutting parameters on the width and structure of free-surface of the chip were examined. The deformability of material and interaction at the tool-chip contact were also identified. The experimental results showed that high-speed milling produced serrated chip, which was significantly affected by the friction at tool and chip contact.